The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2007
DOI: 10.1080/14622200701484961
|View full text |Cite
|
Sign up to set email alerts
|

Does how you quit affect success? A comparison between abrupt and gradual methods using data from the International Tobacco Control Policy Evaluation Study

Abstract: Two recommended quit methods in standard cessation programs involve either gradual reduction of smoking prior to complete abstinence ("cut down") or abrupt abstinence from cigarettes ("cold turkey"). This study examined the reported use, characteristics of users, and the impact of self-selected strategy choice on quitting success and relapse of adult smokers who reported quitting on their own. Data came from the first three waves of the International Tobacco Control Policy Evaluation 4-Country Survey (ITC-4). … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
68
1
5

Year Published

2009
2009
2015
2015

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 77 publications
(82 citation statements)
references
References 22 publications
8
68
1
5
Order By: Relevance
“…Our finding that abrupt cessation is associated with better outcomes than cutting down replicates similar findings from earlier waves of the ITC study (Cheong, Yong, & Borland, 2007), and this appears to occur largely independent of the delay between the decision to quit and implementation, something that is surprising. We thought it possible that the period of cutting down might have explained some differential success rate by delay in actually quitting.…”
Section: Discussionsupporting
confidence: 78%
“…Our finding that abrupt cessation is associated with better outcomes than cutting down replicates similar findings from earlier waves of the ITC study (Cheong, Yong, & Borland, 2007), and this appears to occur largely independent of the delay between the decision to quit and implementation, something that is surprising. We thought it possible that the period of cutting down might have explained some differential success rate by delay in actually quitting.…”
Section: Discussionsupporting
confidence: 78%
“…Thus, for pregnant smokers, an SMS intervention might need to be supplemented. Adding scheduled gradual reduction (SGR) might help pregnant women, most of whom have already reduced their smoking (England et al, 2001) but cannot quit (Pickett, Rathouz, Kasza, Wakschlag, & Wright, 2005) because "self-weaning" often undermines cessation (Cheong, Yong, & Borland, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…Some studies found that most smokers used the abrupt method in their most recent quit attempt (Cheong et al, 2007;Hughes, 2007;Hyland et al, 2004;Shahab et al, 2009), but others found that half or more of the smokers who planned to quit were interested in gradual rather than abrupt cessation Peters et al, 2007;Shiffman et al, 2007), and that at any time point, most smokers were attempting smoking reduction (Beard et al, 2011). Smokers' preferences may also fluctuate over time (Peters and Hughes, 2009) or geographically.…”
Section: Preference For Abrupt or Gradualmentioning
confidence: 99%
“…Several observational studies found that smoking abstinence rates were higher in smokers who quit abruptly than in those who quit gradually (Cheong et al, 2007;Fiore et al, 1990;Glasgow et al, 1985;Peters et al, 2007;West et al, 2001). However, in observational studies, associations may be explained by confounding variables such as motivation to quit, self-efficacy, dependence level, or the amount of support received, as those who used the gradual method may have been less likely to receive professional support, since gradual cessation is not recommended by most treatment guidelines (Fiore, 2008;West et al, 2000).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation